All Days 2012
DOI: 10.4043/22963-ms
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Inflow Control Devices Configurations for Oil Rim Reservoirs

Abstract: Judicious selection of intelligent completions will increase oil recovery andconstrain unwanted water and gas production from the reservoir. Field experience, and results from extensive simulation studies, shows that thewater, oil and gas production are highly dependent on the type of inflowcontrol devices (ICDs) and the ICD configuration. Therefore, choosing the bestICD configuration is a key point to maximize the total oil production. In along horizontal well the primary objective is to max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…IT has been observed from actual field experience and outcome from the extensive simulation studies that the oil, water and gas production are extremely reliant on the type and arrangement of ICD (Mojaddam et al 2012). A suite of optimized ICD modeling workflows and evaluation tools were developed to address these issues using a plug-in architecture in an industry-leading exploration and production platform (Schlumberger PETREL 2015) and reservoir simulator Historically, the most common method for designing ICD completions has been to use steady-state or pseudo steady-state (i.e.…”
Section: Sensitivity Study Of Inflow Control Devicecompartment Lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…IT has been observed from actual field experience and outcome from the extensive simulation studies that the oil, water and gas production are extremely reliant on the type and arrangement of ICD (Mojaddam et al 2012). A suite of optimized ICD modeling workflows and evaluation tools were developed to address these issues using a plug-in architecture in an industry-leading exploration and production platform (Schlumberger PETREL 2015) and reservoir simulator Historically, the most common method for designing ICD completions has been to use steady-state or pseudo steady-state (i.e.…”
Section: Sensitivity Study Of Inflow Control Devicecompartment Lengthmentioning
confidence: 99%
“…Results obtained from fields and simulation studies show that production of oil, gas, and water is very much dependent on the type of ICD and number of ICD used (Mojaddam Zadeh et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Spiral-type ICDs use a number of helical channels or labyrinthine pathways of a predefined length and diameter, to impose a pressure drop due to surface friction (Li et al 2011). The pressure drop Δp s (all units are given in the Nomenclature at the end of the chapter) across a spiral-type ICD is defined using the following empirical relationship (Youngs et al 2009;Schlumberger 2011) Consistent with previous studies, we use 5 different ICD strengths (a s ) which correspond to nominal pressure drop ratings of 0.2, 0.4, 0.8, 1.6 and 3.2 bar, for a 12m long ICD flowing 26 Sm 3 /day (Henriksen et al 2006;Mojaddam Zadeh et al 2012).…”
Section: Well Modelmentioning
confidence: 99%
“…This is presented in Figure 3. Mojaddam et al (2012), in their paper titled "optimal inflow control devices configurations for oil rim reservoirs" indicated that the primary objective in every ICD modeling is to maximize oil production from the whole completion interval and that effective design process should be put in place to avoid losses in production and recovery. Skin is defined as a drawdown which is not accounted for in terms of barrels.…”
Section: Introductionmentioning
confidence: 99%